EFFECT OF LOADING FREQUENCY ON FATIGUE BEHAVIOR OF MAGNESIUM ALLOY IN HUMID ENVIRONMENT (Jurnal Mekanikal, 2018)
Effect of loading frequency on fatigue behavior of an extruded AZ61 magnesium alloy was investigated at 50C-80%RH environment. The frequencies applied were I and 10 Hz. It was found that at stresses below the fatigue limit (at 20C-55%RH) , the fatigue fracture was time dependent where fatigue lives f or both frequencies were almost identical. In contrast, the fotigue fracture in the region higher than the fatique limit was dominated by Ihe number of loading cycles. Fatigue fracture at low stress ampliludes for both frequencies were originated from the corrosion pit formed on the surface. Effect off requency on fatigue crack growth behavior was also investigared. The results showed that in the near-threshold region, the I Hz f requency demonstrated higher fatique crack. growth resistance compared to the 10 Hz.
Keywords: Fatigue; frequency; environment; corrosion pit. magnesium alloy.